2020
DOI: 10.3390/s20247321
|View full text |Cite
|
Sign up to set email alerts
|

Fisheye-Based Smart Control System for Autonomous UAV Operation

Abstract: Recently, as UAVs (unmanned aerial vehicles) have become smaller and higher-performance, they play a very important role in the Internet of Things (IoT). Especially, UAVs are currently used not only in military fields but also in various private sectors such as IT, agriculture, logistics, construction, etc. The range is further expected to increase. Drone-related techniques need to evolve along with this change. In particular, there is a need for the development of an autonomous system in which a drone can det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In general terms, it can be said that the data that predominate in the military context are more complex to process than those in a conventional organization. In the study we have carried out, the main sources found are biometric data, e.g., from electroencephalograms [70]; data from military experts and commanders (e.g., field assessments and weaponry needed in that particular field), which should be used in conjunction with the other data to build decision systems [35]; the Internet of things, smart and connected devices widely used by the military, generating large volumes of information over time [71], e.g., those provided by radars [72]; the Internet of battlefield things, which connects soldiers with smart technology in weapons and other objects to give troops "extra sensory powers" [73]; military personnel data, e.g., those obtained in screening interviews [74]; military veterans' data obtained, e.g., from their administrative personal files [75]; and other data, both internal and open in any format (including videos, images and speeches), e.g., those coming from unmanned aerial vehicles [76], videos for facial recognition [77,78], data from the Internet, etc. ; -Insight generation for military.…”
Section: Discussionmentioning
confidence: 99%
“…In general terms, it can be said that the data that predominate in the military context are more complex to process than those in a conventional organization. In the study we have carried out, the main sources found are biometric data, e.g., from electroencephalograms [70]; data from military experts and commanders (e.g., field assessments and weaponry needed in that particular field), which should be used in conjunction with the other data to build decision systems [35]; the Internet of things, smart and connected devices widely used by the military, generating large volumes of information over time [71], e.g., those provided by radars [72]; the Internet of battlefield things, which connects soldiers with smart technology in weapons and other objects to give troops "extra sensory powers" [73]; military personnel data, e.g., those obtained in screening interviews [74]; military veterans' data obtained, e.g., from their administrative personal files [75]; and other data, both internal and open in any format (including videos, images and speeches), e.g., those coming from unmanned aerial vehicles [76], videos for facial recognition [77,78], data from the Internet, etc. ; -Insight generation for military.…”
Section: Discussionmentioning
confidence: 99%
“…However, traditional VIN-based algorithms cannot cover a wide area. Thus, in this paper, we adopted a hierarchical VIN [22] method for path planning to cover a large target area such as our test fields (4 km × 4 km and 1 km × 1 km).…”
Section: Autonomous Path Planningmentioning
confidence: 99%
“…In recent years, we have seen rapid development in the field of autonomous vehicles. Scientists are conducting intensive research on vehicle autonomy in various environments: water [1,2], ground [3][4][5][6], and air [7][8][9][10]. The vast majority of vehicle autonomy is based on meters and sensors.…”
Section: Introductionmentioning
confidence: 99%